Characterization of the virome of shallots affected by the shallot mild yellow stripe disease in France. - Armelle Marais; Chantal Faure; Sébastien Theil; Thierry Candresse (PLoS ONE, 2019)
To elucidate the etiology of a new disease of shallot in France, double-stranded RNAs from asymptomatic and symptomatic shallot plants were analyzed using high-throughput sequencing (HTS). Annotation of contigs, molecular characterization and phylogenetic analyses revealed the presence in symptomatic plants of a virus complex consisting of shallot virus X (ShVX, Allexivirus), shallot latent virus (SLV, Carlavirus) and two novel viruses belonging to the genera Carlavirus and Potyvirus, for which the names of shallot virus S (ShVS) and shallot mild yellow stripe associated virus (SMYSaV), are proposed. Complete or near complete genomic sequences were obtained for all these agents, revealing divergent isolates of ShVX and SLV. Trials to fulfill Koch's postulates were pursued but failed to reproduce the symptoms on inoculated shallots, even though the plants were proved to be infected by the four viruses detected by HTS. Replanting of bulbs from SMYSaV-inoculated shallot plants resulted in infected plants, showing that the virus can perpetuate the infection over seasons. A survey analyzing 351 shallot samples over a four years period strongly suggests an association of SMYSaV with the disease symptoms. An analysis of SMYSaV diversity indicates the existence of two clusters of isolates, one of which is largely predominant in the field over years.